Pengaruh Gaya Mengajar Dosen terhadap Prestasi Belajar Mahasiswa Univesitas Stella Maris Sumba - Yeyen Asrafil Ula; Marlin Nanga; Paulina Putri Bora; Marten Bili; Yohanes Toda Ngongo; Rikardas Saraswati Bili; Melkianus Mone (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
This study aims to determine the effect of lecturers' teaching styles on student achievement at Stella Maris University, Sumba. The research method used is quantitative with a survey approach through questionnaires and observations. Lecturers' teaching styles are categorized into four types, namely facilitator, demonstrator, delegator, and authoritarian styles. The results of the observation show that the facilitator style is the most dominant style used (45%), followed by demonstrator (35%), delegator (15%), and authoritarian (5%). Data analysis using simple linear regression shows an R Square value of 0.468, which means that the lecturer's teaching style explains 46.8% of the variation in student achievement. In addition, a significance value of 0.000 (<0.05) is obtained, which indicates that there is a significant influence between the lecturer's teaching style and student achievement. This finding confirms that the application of the right and participatory teaching style can improve student learning outcomes.